Pós-tratamento de efluentes por processos de separação por membranas e reúso de água em uma indústria de laticínios - Galvão, Douglas Felipe (2016)
The dairy industry uses substantial amount of water to achieve the production process, especially for the maintenance of hygiene and cleanliness conditions. With this, is generating considerable volume of wastewater requiring treatment to meet the discharge standards before discarded. With the shortage of water resources and charging for water use, minimizing water consumption in industries is of paramount importance to maintain its market competitiveness. In this sense, there has been increasing interest in the reuse of wastewater, in order to decrease the good water consumption by processes that do not require such high quality that feature. Membrane separation processes are highlighted in generating good quality reuse water that can meet the demand of various industrial processes. Thus, the present study aimed to evaluate the membrane separation processes such as post-treatment of dairy industry effluent with a view to reuse of this effluent. For this, the physical-chemical and microbiological characterization of the studied dairy wastewater was held, achieving the separation processes microfiltration membranes (MF) and ultrafiltration (UF), and microfiltration followed by ultrafiltration (MF + UF). The MF and UF processes were performed varying the pressure conditions applied, performing the evaluation of the quality of the effluent obtained after the separation of membrane processes, considering the compliance with technical, legal and sanitary requirements for different industrial uses. The results show that the MF and UF processes have considerable effectiveness in the treatment of the effluent from the dairy industry, with efficiencies reached 36.57% for total nitrogen, 98.39% for oils and greases, 97.27% for COD and 97.64% for BOD. The membrane MF demonstrated maximum efficiency in the removal of COD, BOD, ammonia nitrogen, phosphorus, turbidity, total volatile solids, oils and greases of 97.27, 96.79, 73.96, 38.46, 100, 95.89 and 87.79%, respectively. The UF membrane had removal efficiency of COD, BOD, ammonia nitrogen, phosphorus, turbidity, total volatile oils and greases and solids of 97.27, 90.29, 70.81, 20.51, 100, 97.26 and 91.01%, respectively. For membrane MF and UF 100% efficiencies were obtained in the removal of thermotolerant coliforms. For MF tests followed by UF with the best certain operating conditions, were obtained quite considerable results for BOD, COD, turbidity, and total volatile solids, 97.64, 97.29, 93.11 and 100%, respectively. MF and UF membranes showed quite similar permeate fluxes and even with increasing pressure, permeate flows had not very different values, while the two membranes MF and UF has enough influence of fouling on its surface, causing rapid decline in the permeate flux. Even with a pore size smaller than the MF membrane, UF membrane showed higher permeate flux than MF. Comparing the results of physico-chemical parameters and biological of MF and UF processes with the patterns of reuse of wastewater,there was satisfactory compliance with the parameters for reuse in boilers, cooling towers, floor washing, irrigation of green areas, washing vehicles, fire protection and sanitary discharge.